Antisense oligonucleotide gapmers containing phosphoryl guanidine groups reverse MDR1-mediated multiple drug resistance of tumor cells - Maxim S. Kupryushkin; Anton V. Filatov; Nadezhda L. Mironova; Olga A. Patutina; Ivan V. Chernikov; Elena L. Chernolovskaya; Marina A. Zenkova; Dmitrii V. Pyshnyi; Dmitry A. Stetsenko; Sidney Altman; Valentin V. Vlassov (Elsevier, 2022)
Antisense gapmer oligonucleotides containing phosphoryl guanidine (PG) groups, e.g., 1,3-dimethylimidazolidin-2-imine, at three to five internucleotidic positions adjacent to the 3' and 5' ends were prepared via the Staudinger chemistry, which is compatible with conditions of standard automated solid-phase phosphoramidite synthesis for phosphodiester and, notably, phosphorothioate linkages, and allows one to design a variety of gapmeric structures with alternating linkages, and deoxyribose or 2'-O-methylribose backbone. PG modifications increased nuclease resistance in serum-containing medium for more than 21 days. Replacing two internucleotidic phosphates by PG groups in phosphorothioate-modified oligonucleotides did not decrease their cellular uptake in the absence of lipid carriers. Increasing the number of PG groups from two to seven per oligonucleotide reduced their ability to enter the cells in the carrier-free mode. Cationic liposomes provided similar delivery efficiency of both partially PG-modified and unmodified oligonucleotides. PG-gapmers were designed containing three to four PG groups at both wings and a central "window" of seven deoxynucleotides with either phosphodiester or phosphorothioate linkages targeted to MDR1 mRNA providing multiple drug resistance of tumor cells. Gapmers efficiently silenced MDR1 mRNA and restored the sensitivity of tumor cells to chemotherapeutics. Thus, PG-gapmers can be considered as novel, promising types of antisense oligonucleotides for targeting biologically relevant RNAs.